Social Religious Relations of the NU and Muhammadiyah Islamic Communities in the Multicultural Era - Fadzilah, Nurul; Hrp, Arpin Aminuddin; Amal, M. Khusna; Saihan, Saihan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to find out how Nu and Muhammadiyah community organizations form and maintain social relations in the current multicultural era. The method used in this research is a descriptive research method. The data collection technique in this research uses library research. The data collection technique for this research is by searching for data, reading data, marking data, and narrating data related to information contained in books, journals, proceedings, print media and online media. The results of this research state that Nahdlatul Ulama (NU) and Muhammadiyah have a very important role in maintaining and strengthening social relations in the multicultural era in Indonesia. Nu and Muhammadiyah provide education and character development to various educational institutions, emphasizing tolerance and moderation through Islam Nusantara. Nu and Muhammadiyah through their education and lectures often include instilling inclusive national values, respecting diversity as the nation's wealth. Through these various approaches, Nu and Muhammadiyah have succeeded in maintaining and strengthening social relations in the multicultural era in Indonesia. They play an important role in building a more inclusive, tolerant and harmonious society, and respect cultural, religious and ethnic differences as wealth that must be protected and respected.